Analisis In Silico pada VCO untuk Terapi Dermatitis Atopik - Mardiana; Primadhanty B; Adniana N; Halim PK; Didik H. Utomo; Endra Yustin Ellistasari; Suci Widhiati (PT Dexa Medica, 2020)
Introduction: In silico analysis is used in the early stages of drug discovery to speed the rate of discovery that is considered cost and time-efficient. Virgin Coconut Oil (VCO) is a treatment option for atopic dermatitis because it has function to repair skin barrier and as anti-inflammation. Objective: To evaluate the VCO content using computational in silico analysis for the treatment of atopic dermatitis. Methods: The active compounds of Cocos nucifera extracted from KNApSAcK database were predicted experimentally and analyzed computationally using Simple Molecular-Input Line-Entry System (SMILES), Prediction of Activity Spectra for biologically active Substances (PASS) server, and Search Tool for Interactions of Chemicals (STITCH). Results: There are 19 active compounds found in VCO. The analysis shows that VCO has free fatty acid (FFA) protein which acts as a receptor for long and medium chain saturated and unsaturated fatty acids. The highest potential bioactivity of active VCO compounds was as antieczema, with the most important component was linoleic acid, with an average value of probable to be active (Pa) = 0.872, predicted to be highly potential in computational and laboratory tests. Conclusion: Based on this study, we recommend the use of VCO as treatment for atopic dermatitis because VCO has anti-inflammatory potential bioactivity, histamine inhibitor, improves skin barrier function and antieczema which could improve the outcome of atopic dermatitis.